Effect of Bt Transgene on AM Fungi Infection and Yield Attributes of Cotton (Gossypium hirsutum L.) - Beura, Kasturikasen; Pradhan, Amit Kumar; Rakshit, Amitava; Singh, Mahendra (International Journal of Bio-resource and Stress Management, 2015)
A pot experiment was carried out in 2010 during wet season (July to December) at the Institute of Agricultural Sciences, Banaras Hindu University to evaluate the extent of root infection by AM (Arbuscular Mycorrhiza) fungi and yield attributing characteristics of cotton under both Bt (Bacillus thuringiensis) and non-Bt systems under varied soil types. It included three different soil orders i.e. Entisol, Inceptisol and Alfisol. Bt cotton (cv. NCS-138) and its non-transgenic isoline (cv. NCS-138) were grown until maturity. From the results it was evident that among the three different soils, red soil exhibited higher root infection in comparison to alluvial and black soil. Per cent root infection decreased significantly to the extent of 10-13% in Bt crop as compared to non-Bt counterpart and 9.5-15% during the three growth stages. During the intermediate stages of crop growth, there were significant differences in growth parameters and yield attributes between Bt and the non-Bt isoline. It was also observed that the alluvial soil produced higher shoot biomass compared to black and red soil during initial stages of crop growth. But during the intermediate stages of crop cycle, the growth picked up in black soil. In the final stage, alluvial soil produced higher biomass as compared to the black and red soil. At the same time, Bt-cotton plants showed comparatively more root length than non-Bt crop over the entire crop growth stages.